The study on a comparison between customers' expectations and actual performance towards service quality provided by Melaka Stadium Corporation (MSCorp) / Mohd Aziehan Sa'ri (Faculty of Business Management, 2007)
Melaka Stadium Corporation (MSCorp) is under a Melaka State Government which provides all facilities for sports and others too, such as exhibition hall, seminar rooms, business centre and many other facilities. Melaka Stadium Corporation is to plan and organize any event or activity that can generate income for state and sports industry. It is hard for the company to determine which aspect of quality customer' rate most highly since their expectation towards the services quality is different. Customer with high expectation and lack of understanding also give a challenge to the MSCorp This study is concentrate on Comparison between Consumer Expectation and Actual Performance towards Service Quality provided by Melaka Stadium Corporation (MSCorp). This study also clarifies the gap among customer expectation between MSCorp's actual performances and determines the level of the services quality and to study the factors which influences services quality of the MSCorp. The main problem faced by MSCorp is in satisfying the needs and wants of each of their service users. Each of customers has different expectation before using MSCorp service and customer with high expectation give a challenge to the MSCorp. The objectives of this study are to determine the level of service quality, to study the factor which influences service quality toward MSCorp and to recommend methods and ways that can be used to improved service quality. This study used Exploratory as a research design that provides data that help managers discover environmental forces affecting a marketing decision. In this study, the sampling design used IS Nonprobability Sampling and the Convenience Sampling Technique. It based on the selection of readily available respondents. In this study, researcher has written a set of questionnaire and distribute to the respondents. After the questionnaires were completed, the data were coded before it is transferred to the computer for analysis the SPSS programme was being used to analyze the data. According to the findings, MSCorp not meting their Customers' Expectation in those five factor, whereas factors like Reliability, Assurance, Tangibles, Empathy and Responsiveness it still need an improvement from the MSCorp since all these factors unable to meet what customers being expected. Since that , the MSCorp should do an improvement towards increasing their performance so that the MSCorp will achieve excellent performance or excellent service quality in the future.